2005
DOI: 10.1590/s0102-261x2005000200003
|View full text |Cite
|
Sign up to set email alerts
|

O método do potencial espontâneo (SP): uma revisão sobre suas causas, seu uso histórico e suas aplicações atuais

Abstract: ABSTRACT. This paper synthesizes the results of a compilation and integration of the most important papers and textbooks dealing with the self potential method (SP), also taking into account the author experience on the subject. Furthermore, it introduces survey and processing techniques as well as presentation and interpretation modes. A short description of the SP generation processes, related to both mineral exploration and ground water flow studies, is presented. In the former case, the usually negatives S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
0
6
0
3
Order By: Relevance
“…This must be attributed to a concentration of underground flow lines and the creation of a streaming potential. Such streaming potential, or electrofiltration, cause self-potential anomalies and are commonly correlated with relief at the topsoil [18]. Several authors have shown that streaming potential depends on the ionic charge of the flows [31].…”
Section: Self-potential Variations In the Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…This must be attributed to a concentration of underground flow lines and the creation of a streaming potential. Such streaming potential, or electrofiltration, cause self-potential anomalies and are commonly correlated with relief at the topsoil [18]. Several authors have shown that streaming potential depends on the ionic charge of the flows [31].…”
Section: Self-potential Variations In the Landscapementioning
confidence: 99%
“…The self-potential may have various origins. It depends on groundwater flow, an electrokinetic contribution generating a streaming potential, due to the displacement of a mass of water with its ionic charges through porous medium [16][17][18]. The self-potential also depends on redox conditions, an electro-redox contribution generated by the gradient of redox potential in a natural geobattery process [15,[19][20][21] that may prevail near garbage dumps.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of environmental studies, the main application of the SP method is to determine the sense of the groundwater flow (Gallas 2005).…”
Section: Introductionmentioning
confidence: 99%
“…O método de potencial espontâneo é comumente utilizado na identificação de depósitos minerais (CORRY, 1985) e do sentido do fluxo da água subterrânea (BOGOSLOVSKY;OGILVY, 1973;GALLAS, 2005 (BORGES, 2002;BOLINELLI JR., 2004;PORSANI et al, 2004b …”
Section: Lista De Figurasunclassified